Do European regulatory measures accelerate national market access in Belgium? A retrospective analysis of medicines centrally authorised between 2015 and 2020 - Isabelle Huys; Steffen Fieuws; Zilke Claessens; Joël Daems; Liese Barbier (BMJ Open)
Background At the European level, several regulatory measures (ie, priority medicines (PRIME) scheme, accelerated assessment, conditional marketing authorisation and authorisation under exceptional circumstances) are in place with the aim to expedite the marketing authorisation process for medicines targeting unmet medical needs (UMNs). However, the potential impact of these measures on subsequent decisions regarding market access at the national level, and ultimately if medicines making use of these supporting measures reach the patient earlier, remains unclear.Objectives This study seeks to (1) assess the impact of such European regulatory measures on the number of successful applications and time to reimbursement of this group of medicines in the national context of Belgium and (2) evaluate the association between the application of European regulatory measures and Belgian measures (ie, early access pathways and managed entry agreements).Design A total of 322 medicines granted a European centralised marketing authorisation between 2015 and 2020, excluding generic products/biosimilars, were included in the study. For this set of medicines, data on European and Belgian regulatory and market access measures were extracted from the websites of the responsible European and Belgian authorities and completed with requested information up to December 2022. Regression analysis was used to assess the association between the application of European regulations and Belgian measures. Survival and regression analysis was used to test the impact of such regulatory measures on the time to and rate of reimbursement in Belgium.Results From the total sample (n=322), 34% (n=108) received a European regulatory measure, and also 34% (n=108) had a Belgian measure applied. Overall, 63% (n=202) of the total sample was submitted for reimbursement in Belgium, and of these, 83% (n=167) were reimbursed at the time of assessment. The median regulatory assessment time at the European level was approximately 14 months, while the median Belgian reimbursement assessment time was approximately 11 months. The study found that regulatory measures did not significantly impact the European or national assessment times or status. A significant reduction in European regulatory assessment time was observed only in the cases of the PRIME scheme (p=0.0087) and accelerated assessment (p<0.0001). The study also indicated a positive association (p=0.0019) between the application of European measures and the application of Belgian measures. However, this significant association was not found for specific measures individually, with the exception of the accelerated assessment (p<0.0001). Medicines undergoing accelerated assessment were more likely to also receive a Belgian measure.Conclusion This study shows that while European regulatory measures targeting UMNs often trigger corresponding actions in Belgium, this alignment does not necessarily shorten the time from regulatory submission to reimbursement. Lacking submission for reimbursement by pharmaceutical companies appears to be the most frequent reason for absent reimbursement in Belgium. European policy initiatives promoting timely market entry across member states could be crucial for improving patient access.